2017
DOI: 10.1159/000480470
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Inhibits Insulin Signaling in Primary Rat Hepatocytes via the LPA3 Receptor Subtype and is Increased in Obesity

Abstract: Background/Aims: Obesity is a main risk factor for the development of hepatic insulin resistance and it is accompanied by adipocyte hypertrophy and an elevated expression of different adipokines such as autotaxin (ATX). ATX converts lysophosphatidylcholine to lysophosphatidic acid (LPA) and acts as the main producer of extracellular LPA. This bioactive lipid regulates a broad range of physiological and pathological responses by activation of LPA receptors (LPA1-6). Methods: The activation of phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Two very recent studies have provided more direct evidence for an inhibitory role of ATX-LPA signaling on tissue insulin function (21,44). Acute pretreatment of primary rat hepatocytes with LPA decreased insulin-stimulated AKT phosphorylation, glucokinase, and SREBP-1c expression, PI3K activation, and glycogen synthesis, likely via LPA1 and/or LPA3 (44). Moreover, inhibition of ATX protected against interleukin 6-induced impairment of insulin-stimulated AKT phosphorylation in 3T3-L1 adipocytes (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two very recent studies have provided more direct evidence for an inhibitory role of ATX-LPA signaling on tissue insulin function (21,44). Acute pretreatment of primary rat hepatocytes with LPA decreased insulin-stimulated AKT phosphorylation, glucokinase, and SREBP-1c expression, PI3K activation, and glycogen synthesis, likely via LPA1 and/or LPA3 (44). Moreover, inhibition of ATX protected against interleukin 6-induced impairment of insulin-stimulated AKT phosphorylation in 3T3-L1 adipocytes (21).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few prior studies have examined the effect of ATX-LPA signaling on tissue insulin function (21,24,44). Rancoule et al (24) showed that administration of a LPA1/3 receptor antagonist in high-fat diet-fed mice for 3 weeks improves insulin sensitivity and increases insulinstimulated glucose oxidation in muscle ex vivo, suggesting that LPA signaling through LPA1/3 impairs muscle insulin function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both environmental factors and genetic susceptibility contribute to insulin sensitivity and resistance, the regulation of AKT activity may play a pivotal role in insulin-mediated signal transduction because mice lacking Akt develop diabetes due to their resistance to insulin signaling [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…LPA is able to attenuate insulin signaling in rat hepatocytes via LPA 3 signaling through decreased hepatocyte glucose uptake and glycogen synthesis [ 91 ]. In the same study, the authors reported LPA 16:0 concentrations to be about 25 percent higher in obese patients with a body mass index (BMI) >30 compared to normal weight individuals (BMI 18.5–25) [ 91 ].…”
Section: Maladaptive Lpa Signaling In Chronic Inflammatory Diseasementioning
confidence: 99%